2018
DOI: 10.1111/jir.12558
|View full text |Cite
|
Sign up to set email alerts
|

Self‐injurious behaviours in rhesus macaques: Potential glial mechanisms

Abstract: Background: Self-injurious behaviour (SIB) can be classified as intentional, direct injuring of body tissue usually without suicidal intent. In its non-suicidal form it is commonly seen as a clinical sign of borderline personality disorder, autism, PTSD, depression, and anxiety affecting a wide range of ages and conditions. In rhesus macaques SIB is most commonly manifested through hair plucking, self-biting, self-hitting, and head banging. SIB in the form of self-biting is observed in approximately 5–15% of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…412 Likewise, astrocytes with small cell bodies and less complex processes were identified in Rhesus macaques with a self-injurious behaviour. 413 Partial ablation of astrocytes in the prefrontal cortex of healthy rats (by injection of gliotoxin L-α-aminoadipic acid) resulted in the development of depressive-like behaviours, whereas injection of neurotoxin ibotenate did not have such an effect. 404 Ablation of astrocytes also caused secondary damage to neurones translated into impaired working memory and learning.…”
Section: Neuropsychiatric Disorders: Predominance Of Astrocytic Atrop...mentioning
confidence: 99%
“…412 Likewise, astrocytes with small cell bodies and less complex processes were identified in Rhesus macaques with a self-injurious behaviour. 413 Partial ablation of astrocytes in the prefrontal cortex of healthy rats (by injection of gliotoxin L-α-aminoadipic acid) resulted in the development of depressive-like behaviours, whereas injection of neurotoxin ibotenate did not have such an effect. 404 Ablation of astrocytes also caused secondary damage to neurones translated into impaired working memory and learning.…”
Section: Neuropsychiatric Disorders: Predominance Of Astrocytic Atrop...mentioning
confidence: 99%
“…Stereotyped behaviors are the mainfestation of anxious behaviors, typically characterized by repetitive, invariant patterns behavior that lack an obvious goal or function. Macaques can exhibit a wide range of stereotyped behaviors, including pacing, swing, bouncing, self‐biting, self‐grasping, and so on (Hwang et al., 2020 ; also see Bessa Ferreira et al., 2018 ; Ramsey et al., 2018 ). Pacing is a repetitive pattern of activity that follows an invariant path usually involving circling the cage.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary evidence from animal models suggests that glial cells may be involved in regulating behaviours like self-injurious behaviours, which are a frequently seen clinical sign of BPD (385). In one study examining self-injurious macaques, results showed increased vimentin expression on astrocytes and activation of pathways involved in neuroinflammation, tissue remodelling, and cyclic adenosine monophosphate (cAMP) signalling, indicating that glial cells are potential therapeutic targets (386). This is significant, because findings have previously shown that the factor of ED is associated with a history of non-suicidal self-injury in BPD patients; however, this relationship is noted to be complex and precise mechanistical insight is still lacking (387).…”
Section: Linking Inflammation and Ed Via Neuroimaging And Behaviour I...mentioning
confidence: 99%